2021
DOI: 10.1155/2021/5585951
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cortical Plasticity in Schizophrenia by Transcranial Magnetic Stimulation

Abstract: Neural plasticity refers to the capability of the brain to modify its structure and/or function and organization in response to a changing environment. Evidence shows that disruption of neuronal plasticity and altered functional connectivity between distinct brain networks contribute significantly to the pathophysiological mechanisms of schizophrenia. Transcranial magnetic stimulation has emerged as a noninvasive brain stimulation tool that can be utilized to investigate cortical excitability with the aim of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…There is significant evidence regarding the functional connectivity of neural networks connecting brain regions in patients with schizophrenia. Research conducted with transcranial magnetic stimulation technology has demonstrated that there is a malfunction of cortical networks [ 131 , 132 ] thus leading to severe cognitive dysfunction. The occurrence of these abnormalities is determined, most of the time, by the expression of genetic polymorphisms or mutations [ 133 ].…”
Section: Anatomical Changes and Their Impactmentioning
confidence: 99%
“…There is significant evidence regarding the functional connectivity of neural networks connecting brain regions in patients with schizophrenia. Research conducted with transcranial magnetic stimulation technology has demonstrated that there is a malfunction of cortical networks [ 131 , 132 ] thus leading to severe cognitive dysfunction. The occurrence of these abnormalities is determined, most of the time, by the expression of genetic polymorphisms or mutations [ 133 ].…”
Section: Anatomical Changes and Their Impactmentioning
confidence: 99%